Droop-based demand dispatch schedule in smart grid - Ashourpouri, A.; Ghosh, A.; Shahnia, Farhad (2015)
© 2015 IEEE. In a demand dispatch regime, the error between the load demand and supply is reduced continually to zero such that the frequency is maintained close to its rated value. In the demand dispatch (DD) paradigm, loads follow generation to keep the balance between demand and supply for frequency stabilization. This is in contrast to the conventional demand response in which generation comply with the load demand. It has been assumed that different types of aggregated loads are distributed all over the grid, which can act as spinning reserve for the network. These aggregated loads in distribution grid can participate in grid stabilization based on whether they are categorized as dispatchable or non-dispatchable. Different types of dispatchable and non-dispatchable aggregated loads are deployed in a radial network to study their impacts on the system. The proposed method has been validated through PSCAD simulation studies.